Apoptose e proliferação celular em células trofoblásticas (linhagem BeWo) são diferentemente moduladas pelas cepas de Toxoplasma gondii - Angeloni, Mariana Bodini (2009)
Transplacental transmission causes one of the most severe forms of infection with protozoan parasite Toxoplasma gondii. The ability of the parasite to survive intracellularly largely depends on the blocking of different proapoptotic signaling cascade of its host cell. However, alterations in the incidence of apoptosis, during pregnancy, are associated with abnormal placental morphology and function. Thus, were analyzed the incidence of apoptosis and cell proliferation in trophoblastic cell (BeWo line) infected with a high virulent RH and low virulent ME49 strains of T. gondii. For this, immunohistochemistry to determine the apoptosis and cell proliferation index was done. Besides that, was detected active caspase 3 in infected and non-infected cells. Cells infected with RH strain showed an apoptosis index lower than the control, whereas cells infected with ME49 strain this index was higher than non-infected cells. Moreover, were detected active caspase 3 in cells infected with both RH and ME49 strain and in non-infected cell, in all analyzed times of infection. Besides that, the cell proliferation indexes were higher in cells infected with ME49 strain than the index observed in control and RH strain-infected cells. These results suggest that the high virulent strain RH of T. gondii demonstrated a possible mechanism of delay or inhibits the apoptotic process, as an evasion strategy and a mechanism of the parasite to maintenance in the host cell. In contrast, cells infected with ME49 strain presented higher apoptosis index, indicating that this strain have an opposite mechanism and induces apoptosis of the host cell, which can be associated with a protector mechanism of this low virulent strain of T. gondii. So, we concluded that RH and ME49 strain have opposing behaviors in the incidence of apoptosis and cellular proliferation in trophoblastic cells.